(untitled) (Research, Society and Development, 2022)
Bacterial resistance to antibiotics is a global health problem that needs to be resolved through the discovery of new therapeutic strategies. With the advancement of nanotechnology, new formulations have been tested for the ability to potentiate the action of antibiotics of traditional use by delivering more appropriate concentrations or reducing the toxicity of these drugs. In addition, the advent of nanotechnology has allowed new strategies to be implemented to combat microbial resistance, enabling the development of nanoantibiotics with multifunctional, targeted characteristics, greatly increased bactericidal efficiency, reduced toxicity, decreased adverse side effects, increased bioavailability, decreased dose, reduction of antibacterial concentrations. Nanotechnology has great potential for the development of new and improved antibacterials that benefit human health. The objective of this work was to make a bibliographic survey of the most recent formulations tested in nanotechnology to reduce the toxicity of antimicrobials, especially antibacterials, and/or increase their therapeutic effectiveness.